Case Report: Chemotherapy and Radiotherapy Combined With DC-CIK for Pulmonary and Mediastinal Metastases From Nasopharyngeal Carcinoma - Gan, Yi-Xiu; Li, Gui-Hua; Ou, Xue; Wang, Chun-Hui; Du, Qing-Hua (Frontiers in Oncology, 2022)
The optimal treatment for pulmonary and mediastinal metastasis of nasopharyngeal carcinoma (NPC) is still controversial and the therapeutic effect is poor recently. In one case, we demonstrated a long-term survival after postoperative chemo-radiotherapy combined with dendritic cells and cytokine-induced killers (DC-CIK) immunotherapy for pulmonary and mediastinal metastasis from NPC. Baseline characteristics: A 53-year-old female was admitted to our hospital in June 2008. Pathological biopsy revealed a poorly differentiated squamous cell carcinoma located in the nasopharynx with the invasion of internal pterygoid muscles, the sphenoid bone, and unilateral neck lymph node metastasis. No distant metastases were observed. The stage of NPC was T3N1M0 III (AJCC8). The patient received concurrent chemoradiotherapy for primary lesion and neck lymph nodes and achieved complete remission (CR) of the disease after three months. Every 3 months followed-up was carried out. Pulmonary and mediastinal lymph node metastasis was found in July 2009. Then the patient underwent right upper lobectomy and mediastinal lymph node dissection and five cycles of gemcitabine and cisplatin(GP) regimen chemotherapy, following radiotherapy and DC-CIK immunotherapy. Results: After a follow-up time of 13 years, no tumor recurrence or metastasis and severe adverse reactions were found. Conclusion: Postoperative chemotherapy and radiotherapy in combination with DC-CIK immunotherapy may produce a synergistic therapeutic effect on patients with mediastinal lymph nodes metastasis from NPC.